Impact phenomena assessment: Part I – Structural performance of a tanker subjected to ship grounding at the Arctic - Prabowo Aditya Rio; Byeon Jung Hoon; Cho Hyun Jin; Sohn Jung Min; Bae Dong Myung; Cho Joung Hyung (MATEC Web of Conferences, 2018)
The remarkable influence of the global warming to Arctic environment opens a possibility to conduct a voyage from Asia to Europe through the Northern Sea Route (NSR). This option is considered as a decent solution to reduce fuel consumption and increase time efficiency in delivering cargo to the designated destination. However, this alternative comes with a challenge to keep safety of ship structures against an impact with obstacles which are possibly encountered at the Arctic. Solid ice can be considered as a serious threat to the double bottom of ship structures in impact phenomena, especially ship grounding. In this work, a series of grounding calculations are conducted to produce estimation of structural crashworthiness during interaction between double bottom and conical type ice. Material characteristics based on tensile testing of polar class material are applied to calculation and compared with non-polar steel.